Transcription Factors That Control Behavior—Lessons From C. elegans - Godini, Rasoul; Handley, Ava; Pocock, Roger (Frontiers in Neuroscience, 2021)
Behavior encompasses the physical and chemical response to external and internal stimuli. Neurons, each with their own specific molecular identities, act in concert to perceive and relay these stimuli to drive behavior. Generating behavioral responses requires neurons that have the correct morphological, synaptic, and molecular identities. Transcription factors drive the specific gene expression patterns that define these identities, controlling almost every phenomenon in a cell from development to homeostasis. Therefore, transcription factors play an important role in generating and regulating behavior. Here, we describe the transcription factors, the pathways they regulate, and the neurons that drive chemosensation, mechanosensation, thermosensation, osmolarity sensing, complex and sex-specific behaviors in the animal model Caenorhabditis elegans. We also discuss the current limitations in our knowledge, particularly our minimal understanding of how transcription factors contribute to the adaptive behavioural responses that are necessary for organismal survival.